"Autonomous, yet Connected": An esthetic principle explaining our appreciation of product designs. Issue 5 (15th January 2019) - Blijlevens, Janneke; Hekkert, Paul
Abstract: Esthetic principles describe the levels or combination of design dimensions that are esthetically appreciated. Current principles focus on dimensions connected to product design itself (e.g., unity and variety) or dimensions that refer to a product design's relationship to other product designs (e.g., typicality and novelty). However, product design also has a social significance—they help consumers shape their identity—and this social dimension has hitherto been overlooked in research on esthetic appreciation. In this paper, we propose and investigate the social esthetic principle "Autonomous, yet Connected." In four studies, we show that a product's design leads to the highest esthetic appreciation if it strikes an optimal balance between nurturing the two seemingly opposite needs for connectedness and autonomy. Further, we show how conditions of safety and risk moderate the effects of the principle, which suggests our principle may have evolutionary grounding.